Environmental Sustainability Through Corporate Social Responsibility (American Journal of Development Studies, 2023)
This paper pondered on the Corporate Social Responsibility (CSR) Communication of Starbucks Corporation. CSR integrates social and environmental responsibility of the company, anchored with Sustainable Development Goals (SDG) # 11 (Sustainable Cities and Communities) and # 12 (Responsible Consumption and Production). The purpose of this paper was to elucidate the company’s role in environmental preservation through a robust CSR Communication campaign, discussed and critiqued. The study utilized secondary sources for data gathering, analyzed and interpreted using critical analysis.The result of the paper revealed that Starbuck’s report can expand its sustainability efforts in the light of the company’s strong advocacy on climate change. In achieving corporate expansionism, the paper provides robust knowledge on resilience and preservation for a resilient community.